Strategi Peningkatan Efisiensi Operasional dan Daya Saing Bisnis Usaha Laundry Barokah melalui Pemanfaatan Teknologi - Cuandra, Fendy; Dewi, Jenny Kartika (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, small, and medium enterprises (MSMEs), particularly those operating in the laundry service sector, are currently facing increasingly intense competition as well as demands to adapt to the rapid development of digital technology. Laundry Barokah, as one of the MSMEs in Batam City, still experiences several limitations, especially in terms of brand identity, digital promotional activities, and the use of digital payment systems. This study aims to help improve the operational efficiency and business competitiveness of Laundry Barokah through the utilization of digital technology. The methods employed include interviews and direct observation to gain an in-depth understanding of the partner’s conditions and challenges. Based on the analysis results, several implementations were carried out, including the development of a business logo as a visual identity, promotion through Instagram as a digital marketing medium, and the implementation of a digital payment system using QRIS. The results indicate an improvement in business visibility, as reflected by increased reach and interaction on the Instagram account, the emergence of positive customer reviews, and enhanced convenience and efficiency of transactions through non-cash payments. Overall, the utilization of digital technology has proven to have a positive impact on improving operational efficiency, service quality, and the competitiveness of Laundry Barokah.